Participatory Development Planning Process in the Implementation of the Village Law (Case Study of Pekik Nyaring Village, Pondok Kelapa District, Central Bengkulu Regency) - Bambang Agoes Hermanto; Eka Dewi Anggraini; Benardin Benardin (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
The purpose of this study is to see the participatory development planning process for the emergence of programs or activities in Pekik Nyaring village, Pondok Kelapa district, Central Bengkulu regency in the implementation of the Village Law. To see this participatory development planning process, qualitative research tools are used. The results show that the participatory development planning process in Pekik Nyaring village, Pondok Kelapa district, Central Bengkulu regency has been running in accordance with the mandate of the Constitution, both from the socialization, deliberation, and participation stages. However, due to the weak understanding of the Constitution and the capabilities of village heads, village officials, and the community, the results of the participatory planning process are still not optimal. So that the results in the form of a draft RPJMDes for Pekik Nyaring village are still not in accordance with the spirit of the Constitution.